Organic Coffee Supply Chain Management in the San Martin Region of Peru - Ramos Palomino, Edgar David (2017)
The paper is to explore a model of supply chain management organic coffee in San Martin Region, which was by a long-term research project for organic coffee supply chain management in Peru. The investigation was consolidated with items of researchers who have experiences in the evaluation and analysis of the supply chain of agricultural products worldwide; on the other hand, it is also taken into account the risks affecting the development and fluency through whole supply chain. The contributions here is proposed model of supply chain management organic coffee is suitable for exploring external and internal problems encountered decrease the efficiency of the supply chain. The model is important to analyze and require observations of specialists to collaborate to perform basic modeling that can help solve the problems that improving processes and organizations in the coffee farmers’ cooperatives in the domestic and foreign market, and achieve recognition for their quality and sustainability in Peru.